2020
DOI: 10.1097/sla.0000000000003885
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Complications After Proctectomy for Rectal Cancer

Abstract: Objective: Investigate the association between neoadjuvant treatment strategy and perioperative complications in patients undergoing proctectomy for nonmetastatic rectal cancer. Summary of Background Data: Neoadjuvant SC-TNT is an alternative to neoadjuvant CRT for rectal cancer. Some have argued that short-course radiation and extended radiation-to-surgery intervals increase operative difficulty and complication risk. However, the association between SC-TNT and surgical complications has not been previously i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…Although univariate analyses demonstrated that lower pre-NCRT CEA and CA19-9 levels were potential indicators of a better prognosis, the multivariate analysis proved that only the NSTB score and pathological TNM stage could independently determine the prognosis. In general, pathological indicators had a more robust predictive value than other indicators in determining the prognosis[ 8 ]; however, the multivariate analysis revealed that the NSTB score could predict outcomes better than pathological characteristics of lymphatic invasion, vascular invasion, nerve infiltration, and CRM invasion. Thus, we propose that the NSTB score should be used to guide the treatment and determine the prognosis of patients with RC of clinical stage II/III.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although univariate analyses demonstrated that lower pre-NCRT CEA and CA19-9 levels were potential indicators of a better prognosis, the multivariate analysis proved that only the NSTB score and pathological TNM stage could independently determine the prognosis. In general, pathological indicators had a more robust predictive value than other indicators in determining the prognosis[ 8 ]; however, the multivariate analysis revealed that the NSTB score could predict outcomes better than pathological characteristics of lymphatic invasion, vascular invasion, nerve infiltration, and CRM invasion. Thus, we propose that the NSTB score should be used to guide the treatment and determine the prognosis of patients with RC of clinical stage II/III.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological findings were generally recognized as the most effective indicators to predict the prognosis[ 8 ]. A previous study revealed that lymphatic invasion, perineural invasion, vascular invasion, CRM invasion, LN metastasis, and a higher tumor invasion stage can predict a worse outcome[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…nCRT followed by surgery with a total mesorectal excision is the recommended treatment for patients with locally advanced rectal cancer. nCRT has been proven to be effective to downstage the primary tumor which may facilitate complete resection with negative surgical margins and significantly reduce local recurrence [ 1 , 2 ]. The efficacy of nCRT varies among individual patients ranging from pathological complete response (pCR; defined as ypT0N0) to progression of disease.…”
Section: Introductionmentioning
confidence: 99%